Bioelectronics: Water Soluble Cationic Poly(3, 4‐Ethylenedioxythiophene) PEDOT‐N as a Versatile Conducting Polymer for Bioelectronics (Adv. Electron. Mater. 10/2020). (9th October 2020) - Minudri, Daniela; Mantione, Daniele; Dominguez‐Alfaro, Antonio; Moya, Sergio; Maza, Eliana; Bellacanzone, Christian; Antognazza, Maria Rosa; Mecerreyes, David
Abstract : PEDOT‐N, a water‐soluble cationic conducting polymer for bioelectronics, is presented by David Mecerreyes and co‐workers in article number 2000510 . The water solubility of PEDOT‐N and its cationic nature allows its processability in the form of thin films obtained by the layer‐by‐layer technique or as conducting hydrogels. Its electronic properties and good biocompatibilty shows potential in bioelectronic devices such as biosensors, tissue engineering or drug delivery.